Ernest Hemingway : A New Life - Hutchisson, James M. (Book collections on Project MUSE., 2016)
"A biography of Ernest Hemingway that places his life and art in the defining contexts of the women and places that were important to him, and the pattern of mental illness and suicide in his family"--Provided by publisher.